2021
DOI: 10.1186/s13213-020-01616-2
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequences of two Streptomyces albidoflavus strains DEF1AK and DEF147AK with plant growth-promoting and biocontrol potential

Abstract: Purpose Bacteria belonging to the Streptomyces genus can be exploited in environmentally friendly approaches to food safety. Genome information can help to characterize bioactive strains opening the possibility to decipher their mechanisms of action. Methods The biocontrol and plant growth-promoting activity of two Streptomyces spp. strains, DEF1AK and DEF147AK, were assessed in vitro and in planta. The genome sequences were determined using the Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Although a few studies have been carried out to assess the biocontrol efficacy and mechanism of Streptomyces spp. [ 17 , 18 ], to date there has been no research related to the control of soil-borne pathogens on fennel crops.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have been carried out to assess the biocontrol efficacy and mechanism of Streptomyces spp. [ 17 , 18 ], to date there has been no research related to the control of soil-borne pathogens on fennel crops.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that huth is duplicated in S. parvulus SX6, which may convert the phenylalanine to yield cinnamic acid. A recent study demonstrated that many duplicated genes, such as ABC transporters, contributed to fitness improvements of Streptomyces albidoflavus DEF1AK in planta conditions (Kunova et al 2021). Thus, this finding supports the well-known assumption that gene duplication acts as a mechanism of genomic adaptation to a changing environment (Bratlie et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces are soil-inhabiting, free living, Gram-positive filamentous bacteria that also present as symbionts of plants, insects, and animals ( 1 ). Due to their production of a broad range of bioactive secondary metabolites, Streptomyces have gained attraction in agriculture as biocontrol agents ( 2 9 ).…”
Section: Announcementmentioning
confidence: 99%